1994
DOI: 10.1128/iai.62.12.5464-5469.1994
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii attachment increases expression of fibronectin-binding integrins on cultured lung cells

Abstract: Pneumocystis carinii is an extracellular pathogen which requires attachment to alveolar epithelial cells for growth and replication. Previous studies have demonstrated that the extracellular matrix protein fibronectin (Fn) facilitates attachment of P. carinii to lung cells. This study addresses the role of cell surface Fn receptors (integrins) as mediators of P. carinii attachment and demonstrates the effect of P. carinii attachment on integrin expression on cultured lung cells. To determine the role of Fn-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The direct effects of PC on alveolar epithelial cell function have not been thoroughly investigated. Recent studies from our laboratory have demonstrated PC-induced changes in lung cell integrin expression [35] that may play a role in the pathogenesis of PC pneumonia. Our current study gives further evidence for a role of alveolar epithelial cell-derived factors in the response to PC infection.…”
Section: Figurementioning
confidence: 99%
“…The direct effects of PC on alveolar epithelial cell function have not been thoroughly investigated. Recent studies from our laboratory have demonstrated PC-induced changes in lung cell integrin expression [35] that may play a role in the pathogenesis of PC pneumonia. Our current study gives further evidence for a role of alveolar epithelial cell-derived factors in the response to PC infection.…”
Section: Figurementioning
confidence: 99%
“…Enhanced phagocytosis due to P. carinii opsonization with specific Ab to surface structures [30,31] may be only one possible consequence. Blocking surface molecules such as vitronectin-and fibronectin-binding integrins, which are important for P. carinii attachment to host cells [32][33][34][35], could also impede parasite growth. Furthermore, host cell injury as a consequence of parasite adherence [36,37] could be prevented by these Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface ¢bronectin binding receptors of the integrin family have been identi¢ed. Pottratz et al showed that antibodies towards the ¢bronectin binding K v and K S integrin subunits signi¢cantly inhibited attachment of whole organisms [19]. Further, rat P. carinii organisms and MSG upregulated the expression of K S integrin subunits on A549 cells, and anti-MSG antibody attenuated K S integrin expression, suggesting that MSG is involved in upregulation and expression of molecules that mediates organism-cell attachment.…”
Section: Role Of Msg In Organism Attachmentmentioning
confidence: 99%